New Plant Breeding Techniques in Citrus for the Improvement of Important Agronomic Traits. A Review - Salonia, Fabrizio; Ciacciulli, Angelo; Poles, Lara; Pappalardo, Helena Domenica; La Malfa, Stefano; Licciardello, Concetta (Frontiers in Plant Science, 2020)
New plant breeding techniques (NPBTs) aim to overcome traditional breeding limits for fruit tree species, in order to obtain new varieties with improved organoleptic traits and resistance to biotic and abiotic stress, and to maintain fruit quality achieved over centuries by (clonal) selection. Knowledge on the gene(s) controlling a specific trait is essential for the use of NPBTs, such as genome editing and cisgenesis. In the framework of the international scientific community working on fruit tree species, including citrus, NPBTs have mainly been applied to address pathogen threats. Citrus could take advantage of NPBTs because of its complex species biology (seedlessness, apomixis, high heterozygosity, and long juvenility phase) and aptitude for in vitro manipulation. To our knowledge, genome editing in citrus has successfully induced resistance to Citrus bacterial canker in sweet orange and grapefruit using the resistance gene CsLOB1. In the future, NPBTs will also be used to improve fruit traits, making them healthier. The regeneration of plants following the application of NPBTs is a bottleneck, making it necessary to optimize the efficiency of current protocols. The strengths and weaknesses of using explants from young in vitro plantlets, and from mature plants, will be discussed. Other major issues addressed in this review are related to the requirement for marker-free systems and shortening the long juvenility phase. This review aims to summarize methods and approaches available in the literature that are suitable to citrus, focusing on the principles observed before the use of NPBTs.